Zofia Garlicka: gynecologist and activist for women and motherhood - Kiedrowska, Kaja; Karaś, Radosław; Lepich, Tomasz (Nursing Problems / Problemy Pielęgniarstwa, 2025)
Zofia Garlicka, as a female gynecologist, was highly regarded for her diligence, fairness, tact, and courage. She emphasized the im-portance of the health of pregnant women and respect for motherhood, as well as the significance of quality care for infants, children, and women working in factories. She frequently engaged in social initiatives aimed at establishing modern care facilities for mothers and children. She worked to increase the number of qualified midwifery staff in Poland to improve healthcare services. Zofia Garlicka received her medical education in Geneva, Zurich, and Kraków, learning gynecology and obstetrics at Professor Henryk Jordan’s clinic. During World War II, while imprisoned in Pawiak, she assisted pregnant women. She died in Auschwitz-Birkenau at the age of 68.